2015
DOI: 10.1177/0885328215601926
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide/manganese ferrite nanohybrids for magnetic resonance imaging, photothermal therapy and drug delivery

Abstract: Superparamagnetic manganese ferrite (MnFe2O4) nanoparticles have been deposited on graphene oxide (GO) by the thermal decomposition of manganese (II) acetylacetonate and iron (III) acetylacetonate precursors in triethylene glycol. The resulting GO/MnFe2O4 nanohybrids show very low cytotoxicity, negligible hemolytic activity, and imperceptible in vivo toxicity. In vitro and in vivo magnetic resonance imaging experiments demonstrate that GO/MnFe2O4 nanohybrids could be used as an effective T2 contrast agent. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…IONs can be combined with other inorganic nanoparticles such as molybdenum sulfide [ 72 , 73 ], manganese [ 74 ], copper/selenium [ 75 , 76 ], graphene oxides [ 77 , 78 ], manganese and graphene oxide [ 79 ], Prussian blue [ 80 , 81 ], and copper sulfide [ 82 ].…”
Section: Iron Oxide Nanoparticles For Photothermal Therapymentioning
confidence: 99%
“…IONs can be combined with other inorganic nanoparticles such as molybdenum sulfide [ 72 , 73 ], manganese [ 74 ], copper/selenium [ 75 , 76 ], graphene oxides [ 77 , 78 ], manganese and graphene oxide [ 79 ], Prussian blue [ 80 , 81 ], and copper sulfide [ 82 ].…”
Section: Iron Oxide Nanoparticles For Photothermal Therapymentioning
confidence: 99%
“…Some researchers illustrated that the Mn-ferrite (MnFe 2 O 4 ) decorated GO nanocomposites for clinical applications [49]. It was revealed that the magnetic properties of the ferrites could be effectively used as an superlative hyperthermia and T2 contrast MRI agent.…”
Section: Graphene-based Nanocomposites For Biomedical Applicationsmentioning
confidence: 99%
“…In addition, compared to other carbon nanomaterials, graphene oxide has many merits, such as outstanding water solubility and physicochemical stability owing to its oxygen functional groups, and easy to obtain because of an abundant and low manufacture cost material. [56][57][58][59] Application of UMTD in Tumor Treatment Tumor…”
Section: Photosensitive Ultrasound Contrast Agentmentioning
confidence: 99%